Clinical Correlation Between Inferior Vessel Occlusion and Arrhythmia Incidence in Acute Coronary Sundrome Patients - Biembee Nayoan Cosa Aranda; Ragil Nur Rosyadi (Journal of World Science, 2026)
Background: Arrhythmia is a frequent acute complication in patients with Acute Coronary Syndrome (ACS) and significantly contributes to morbidity and mortality. Myocardial ischemia, autonomic imbalance, and structural myocardial injury lead to electrical instability that may trigger supraventricular and ventricular arrhythmias. Local data evaluating the relationship between arrhythmia incidence and coronary lesion location remain limited and are essential for improving risk stratification, monitoring, and therapeutic strategies. Objective: To evaluate the burden of arrhythmia incidence in ACS patients and examine its correlation with coronary vessel involvement at Dr. Ramelan Naval Hospital, Surabaya. Methods: A prospective clinical study was conducted on 150 ACS patients treated between January and July 2024. Patients were categorized according to diagnosis (NSTEMI or STEMI), gender, age group (<60 years and ?60 years), and coronary lesion location (anterior, lateral, inferior) based on ECG and coronary catheterization findings. Arrhythmia incidence was analyzed using descriptive frequency distribution across subgroups. Results: Most patients were male (72%) and younger than 60 years (57%). Among 113 NSTEMI patients, 63 (42%) developed arrhythmias, predominantly right bundle branch block (RBBB), atrial fibrillation, and sinus bradycardia. In 37 STEMI patients, 26 (18%) experienced arrhythmias, mainly ventricular tachycardia (VT) and sinus bradycardia. Arrhythmias were more frequent in men. Inferior coronary lesions were associated with the highest arrhythmia rate (34%), compared to anterior (19%) and lateral (7%) lesions. Conclusion: Arrhythmias are common in ACS, particularly NSTEMI and inferior infarction. Age, gender, and lesion location are key predictors for determining intensive monitoring and optimal management strategies.